Cellulose/nanocellulose superabsorbent hydrogels as a sustainable platform for materials applications: A mini-review and perspective. (1st January 2023) - Zhang, Zhen; Abidi, Noureddine; Lucia, Lucian; Chabi, Sakineh; Denny, Christian T.; Parajuli, Prakash; Rumi, Shaida Sultana
Abstract: Superabsorbent hydrogels (SAH) are crosslinked three-dimensional networks distinguished by their super capacity to stabilize a large quantity of water without dissolving. Such behavior enables them to engage in various applications. Cellulose and its derived nanocellulose can become SAHs as an appealing, versatile, and sustainable platform because of abundance, biodegradability, and renewability compared to petroleum-based materials. In this review, a synthetic strategy that reflects starting cellulosic resources to their associated synthons, crosslinking types, and synthetic controlling factors was highlighted. Representative examples of cellulose and nanocellulose SAH and an in-depth discussion of structure-absorption relationships were listed. Finally, various applications of cellulose and nanocellulose SAH, challenges and existing problems, and proposed future research pathways were listed. Graphical abstract: Unlabelled Image